E protein binding at the Tcra enhancer promotes Tcra repertoire diversity - Mihai, Ariana; Roy, Sumedha; Krangel, Michael S.; Zhuang, Yuan (Frontiers in Immunology, 2023)
V(D)J recombination of antigen receptor loci is a highly developmentally regulated process. During T lymphocyte development, recombination of the Tcra gene occurs in CD4+CD8+ double positive (DP) thymocytes and requires the Tcra enhancer (Eα). E proteins are known regulators of DP thymocyte development and have three identified binding sites in Eα. To understand the contribution of E proteins to Eα function, mutants lacking one or two of the respective binding sites were generated. The double-binding site mutant displayed a partial block at the positive selection stage of αβ T cell development. Further investigation revealed loss of germline transcription within the Tcra locus at the Jα array, along with dysregulated primary and impaired secondary Vα-Jα rearrangement. Eα E protein binding increases Tcra locus accessibility and regulates TCRα recombination, thus directly promoting Tcra repertoire diversity.